Biotechnological approach to produce riboflavin enriched iru – using riboflavin overproducing Bacillus subtilis. Issue Volume 1(2019)Issue A (8th March 2019) - Olanbiwoninu, Afolake; Greppi, Anna; Lacroix, Christophe; Jans, Christoph
Abstract : Dietary deficiencies are major cause of malnutrition in the developing world, particularly vitamins deficiencies such as riboflavin, which lead to various health disorders. Traditional plant fermentation and their indigenous starter cultures such as Bacillus subtilis might provide solutions to bioenrich riboflavin. We aimed to investigate this idea on the example of B. subtilis derived from iru an alkaline fermented condiment playing an important role in rural Nigeria. After initial isolation, identification and safety assessment, roseoflavin exposure was used to obtain riboflavin overproducing mutants. These were further analysed for functional characteristics. Bàcillus species' (n- 123) were isolated from iru. Initial riboflavin production in supportive growth medium ranged from 50.3 to 479.0 µg l −1 for 27 out of 123 strains evaluated. Subsequent gràdual exposure to 200 mg l −1 roseoflavin increased riboflavin production in the three best producing strains from 350 µg l −1 to 542 µg l −1, 479 µg l −1 to 580 µg l −1 and 362 µg l −1 to 618 µg l −1 . This increased riboflavin in lab-scàle iru fermentation by over 150 percent to 0.12–0.14 mg g −1 and near the recommended daily intake while retaining desired proteolytic and esterase activity. This research provides important proof of concept for the bioenrich the of traditional B. subtilis based plant fermentations used across sub-Saharan Africa and possibly other areas globally.